Análisis del sistema “Control de viajes y tarifas” de la compañía transporte de carga pegaso s.a. del cantón Montalvo - Sánchez Castro, Washington Romeo (2019)
At present, technological tools have become one of the most important factors in terms of the institutional uses of companies, these are used daily for information management. The present case study will analyze the inconveniences presented in the software in a superficial way of the “travel and fares control” computer system of Compañía Transporte de Carga Pegaso S.A. of the Canton Montalvo, analyzing each of the modules and reports generated by the systems. Given the growing demand for transport logistics, and therefore the growth in billing and documentation of partners and customers within the company, the company installed a “travel and fares” computer system that was facilitated by the Provincial Transportation Chamber de Los Ríos, whose objective was to improve the internal processes of its associates and thus obtain a better performance within the institutions. The main problem presented by the installed system that currently has the Compañía Transporte de Carga Pegaso S.A. of the Canton Montalvo, is the Route module that would serve to enter the destinations and origins of the cargo, its weight, its value, the type of cargo and dates of departure and arrival of the merchandise to its destination, another module that presents faults is the Load Order module, this module lacks information since it is linked to the Route module, so the reports are incomplete. There is a module that is not used as is the one of Workshops, since being a company of many partners each one of them carries out its preventive and corrective repairs and maintenance in the workshop of their best choice and in the city they want